Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae) - Ng, Heok Hee (Zootaxa, 2007)
Botia udomritthiruji sp. nov. is described from the Tenasserim River drainage in southern Myanmar. It can be distinguished from congeners by its color pattern, consisting of five dark vertical bars on the body, with the central portion of these bars paler than its edges; with increasing age, the edges of these bars become more irregular and darker, and irregular dark spots on the pale interspaces begin to form, sometimes fusing with the edges of the vertical bars. In morphology, it differs from congeners by a combination of: body depth at anus 23.4–27.7% SL, caudal peduncle depth 15.9– 18.7% SL, and 12 dorsal-fin rays. Evidence for considering B. macrolineata a junior synonym of B. dario and for considering B. rostrata a species distinct from B. almorhae is also presented here.